2016
DOI: 10.4018/ijgcms.2016070104
|View full text |Cite
|
Sign up to set email alerts
|

A Phenomenological Study of Games, Simulations, and Virtual Environments Courses

Abstract: Educational technology programs from across the United States are offering graduate courses in games, simulations, and virtual environments (GSVE) to their students. However, these courses, until now, have not been systematically studied. This research uses a hermeneutical phenomenological approach to answer the research question: “How do instructors describe their experience teaching GSVE courses?” Five professors of educational technology that have taught GSVE courses were interviewed using a semi-structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, it has been tackled in restricted ways. For example, Ritzhaupt et al (2016) focused primarily on the physical access of students, while Soomro et al (2018) merely reported a validation process of an instrument development and validation to measure faculty's (n.322) information and communication technology access. A more current research presented a qualitative analysis regarding community networks in the context of digital divide during coronavirus disease 2019 (COVID-19) (Rich and Pather, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been tackled in restricted ways. For example, Ritzhaupt et al (2016) focused primarily on the physical access of students, while Soomro et al (2018) merely reported a validation process of an instrument development and validation to measure faculty's (n.322) information and communication technology access. A more current research presented a qualitative analysis regarding community networks in the context of digital divide during coronavirus disease 2019 (COVID-19) (Rich and Pather, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the digital divide has been reported in education, it has been elaborated in a few ways. Studies on the digital divide have been focusing on technological physical access either in schools or at homes (Dolan, 2016;Riel & Schwarz, 2002;Ritzhaupt et al, 2016;Zuppa & Rezzano, 2016). Especially, studies with various aspects of higher education faculties of digital technology are still few (Peña-López, 2010;Soomro et al, 2018).…”
Section: Introductionmentioning
confidence: 99%